2023
DOI: 10.1021/acschemneuro.3c00061
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into the Binding of Different Positron Emission Tomography Tracers to Chronic Traumatic Encephalopathy Tau Protofibrils

Abstract: Chronic traumatic encephalopathy (CTE) is a neurodegenerative disease associated with exposure to repetitive head impacts, and it is neuropathologically defined as the accumulation of abnormally hyperphosphorylated tau (p-tau). Early detection of p-tau in the brain is of great value in the prevention and treatment of CTE. Previous experimental studies reported that positron emission tomography (PET) technique using several tau tracers are available for imaging certain neurodegenerative diseases. However, few s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…Our previous metadynamics simulations for CBD and AD tau protofibrils also indicated very high binding for PMPBB3 . Recently, Qi et al identified that PMPBB3 has the top rank of hydrophobic contacts against other tracers to the 3R/4R chronic traumatic encephalopathy (CTE) tau protofibrils . These results indicated that the combination of buta-1,3-dienyl and benzothiazole in the scaffold of PMPBB3 and PBB3 is a good strategy for binding to the surface sites on both 3R/4R and 4R tau fibrils.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Our previous metadynamics simulations for CBD and AD tau protofibrils also indicated very high binding for PMPBB3 . Recently, Qi et al identified that PMPBB3 has the top rank of hydrophobic contacts against other tracers to the 3R/4R chronic traumatic encephalopathy (CTE) tau protofibrils . These results indicated that the combination of buta-1,3-dienyl and benzothiazole in the scaffold of PMPBB3 and PBB3 is a good strategy for binding to the surface sites on both 3R/4R and 4R tau fibrils.…”
Section: Resultsmentioning
confidence: 71%
“…35 Recently, Qi et al identified that PMPBB3 has the top rank of hydrophobic contacts against other tracers to the 3R/4R chronic traumatic encephalopathy (CTE) tau protofibrils. 48 These results indicated that the combination of buta-1,3-dienyl and benzothiazole in the scaffold of PMPBB3 and PBB3 is a good strategy for binding to the surface sites on both 3R/4R and 4R tau fibrils. The use of 1,3-butadiene to connect the benzothiazole and pyridine rings leads to a longer linear scaffold compared to CBD2115, which is believed to be beneficial for contacting with more fibril chains.…”
Section: Mobility Of Tracer Binding On the Surface Sites Evaluated By...mentioning
confidence: 88%
“…35 This is also confirmed in this study where only patchy and moderately elevated FTP SUVR was observed in former football players and does not follow the typical spatial pattern of tau deposition in clinical/preclinical AD patients. Examination of other tau PET tracers [36][37][38] is warranted, as is the development of tracers specifically targeting CTE tau based on knowledge gained through recent cryo-EM findings, 21,22 as well as studies of molecular docking and dynamics simulations. 31 PET imaging of other pathways such as neuroinflammation 39 in the individuals exposed to substantial RHI is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…The BBB score also predicts potential improvement by modifying the topological polar surface area (TPSA). While the pKa and hydrogen bonding potential of the indole nitrogen in OXD-2115 has been shown to contribute to target a nity, 33 modifying the overall number of HBDs, TPSA, and molecular size are potential ways of improving brain uptake for new pyridinyl-indole analogues of OXD-2115 while maintaining a nity for 4R-tau aggregates. CNS MPO (3.6/6.0) and CNS PET MPO (1.7/6.0) predicted OXD-2314 to be as equally likely to penetrate the BBB as OXD-2115.…”
Section: Bbb Permeabilitymentioning
confidence: 99%
“…32 Additionally, OXD-2115 was computationally shown to have favorable binding characteristics for CTE tau proto brils. 33 OXD-2115 represents a new structural scaffold for 4R-tau PET radiotracer development with high selectivity for 4Rtau aggregates over Aβ plaques, a-synuclein deposits, and other CNS targets.…”
Section: Introductionmentioning
confidence: 99%